Social Media and Communication - Wandi Wandi; Niar Andriana (State Islamic Institute of Bone, Indonesia, 2021)
The social media is a new means of communication that is widely used in today's modern era, with the features that can provide comfort and convenience in its use and at an affordable cost and even provided for free. There are positive and negative impacts caused by the social media, therefore, the researchers are interested in finding out how to understand communication and social media in order to adapt to the changes that occur in today's modern era. The research method employed is in the form of a descriptive literature review, containing theories and relevant concepts to the research problem. It can be concluded that one way to adapt with social media is based on self-awareness and ethics in communicating both in commenting, opinionating, and conveying information, and strengthening rules regarding the use of social media in order to achieve good communication goals.